Nanotube-based adsorbing material and application thereof in resource utilization of waste incineration fly ash
By adsorbing materials based on nano tube, the problem of difficulty in long -term stability and suppression of heavy metals in waste incineration flying ash was solved, and the quality of product quality in heavy metals and the use of product quality in the use of fly ash resource.
Patent Information
- Application Number
- CN202411928970.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-25
AI Technical Summary
When the prior art deals with waste incineration fly ash, it is difficult to suppress the leaching of heavy metals in a long and stable manner, resulting in environmental pollution and health risks, and is costly.
Using adsorption materials based on nano tubes, heavy metal adsorption materials with strong adsorption capacity through acid modification and latex legal system, and achieve stability of heavy metals in the fly ash through coupling mechanical chemistry.
Effectively suppress the immersion of heavy metals in the fly ash, complies with the GB9878 standard, improves the quality of product quality in the use of fly ash resource, avoids heavy metal pollution, and reduces the cost of treatment.
Smart Images

Figure CN119346088A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of heavy metal adsorption materials, and specifically relates to an adsorption material based on nanotubes and application thereof in resource utilization of fly ash from garbage incineration. Background Art
[0002] With the development of waste incineration technology in my country, the output and stockpile of fly ash are large. At present, the problem of resource utilization of fly ash is solved. The main heavy metals studied in fly ash are As, Ba, Be, Cd, Cr, Cu, Hg, Ni, Pb, Se, Zn and other heavy metals, among which Pb and Zn have relatively high content. The main ones that are easy to exceed the standard in fly ash are Cd, Cr, Cu, Ni, Pb, and Zn, which are also the focus of heavy metal research in fly ash. When fly ash comes into contact with water in the external environment, especially acid rain or corrosive liquids, the heavy metals in the fly ash will leach into the liquid, and then enter the ecological environment system, polluting groundwater, rivers, lakes, seas and soil, and finally entering the human body. When the heavy metals in the human body are enriched to a certain concentration, it will cause serious harm to the human body, and even cause lesions and death.
[0003] At present, heavy metals are mainly stabilized by cement solidification and chemical reagent stabilization. Landfill after cement solidification is currently the most convenient method for fly ash disposal. It only requires the fly ash and cement or other gel materials to be mixed with water and then demolded and cured. The resulting cement blocks can be directly landfilled. Because of its convenient operation, cement solidification has been widely used around the world. During the cement solidification process, cement and water undergo hydration reactions to produce hydrated calcium silicate gel (CSH) and ettringite (AFt), which encapsulate the heavy metals in the fly ash and inhibit the leaching of heavy metals. However, the mass and volume of cement products will increase significantly, which will lead to an increase in processing costs. In addition, in the long term, heavy metals such as Cd and Zn in the fly ash are at risk of leaching and do not have long-term stability.
[0004] Chemical reagent stabilization is to transform heavy metals in fly ash into more stable forms, such as inorganic mineral salts or polymer complexes, through chemical reactions, so as to achieve the stabilization of heavy metals. Chemical reagents are mainly divided into inorganic reagents and organic reagents. Chemical reagents are selective for heavy metals, so usually multiple chemical reagents or chemical reagents and cement are used for coordinated treatment, but the cost is relatively high. Summary of the invention
[0005] In order to solve at least one of the above problems, the present invention provides a nanotube-based adsorption material and its application in resource utilization of waste incineration fly ash.
[0006] In order to achieve the above object, the present invention adopts the following technical means: The first aspect of the present invention provides a method for preparing a nanotube-based adsorption material, comprising the following steps: S1. Mix the carbon nanotubes and the acid solution in the ratio of carbon nanotubes: concentrated sulfuric acid: concentrated nitric acid = 1 g: 250 mL: (50-80) mL, and perform ultrasonic treatment; reflux at 60-70°C for 5-6 h, cool and dilute, filter with a filter membrane, wash with distilled water until neutral, dry in a vacuum drying oven, and grind to obtain acid-modified carbon nanotubes; S2. Mix and stir the obtained acid-modified carbon nanotubes according to the weight ratio of acid-modified carbon nanotubes: zinc oxide: water: stearic acid: dispersant = 1: (0.5-1): (130-150): (1-1.2): (1-1.5), perform ultrasonication, add 50-70 g of natural rubber latex and stir evenly, perform ultrasonication again, and obtain a mixed solution; S3, the mixed solution is dried in a vacuum drying oven and then calcined and carbonized; the carbonized adsorbent is ground in a mortar and passed through 200-250 meshes to obtain the final adsorption material.
[0007] In some embodiments of the present invention, the dispersant is one or both of gum arabic and sodium dodecylbenzene sulfonate. In some specific embodiments of the present invention, when two dispersants are mixed, the mass ratio of gum arabic to sodium dodecylbenzene sulfonate is 1:1.
[0008] In some embodiments of the present invention, in steps S1 and S2, the ultrasonic time is 30-60 min.
[0009] In some embodiments of the present invention, in step S1, the drying temperature is 90-100° C. and the drying time is 4-8 hours.
[0010] In some embodiments of the present invention, in step S1, the filter membrane is a 0.22 μm polytetrafluoroethylene filter membrane.
[0011] In some embodiments of the present invention, in step S3, the calcination temperature is 800-850° C., and the carbonization time is 4-6 hours.
[0012] In some embodiments of the present invention, the carbon nanotubes have a length of 2-10 nm.
[0013] The second aspect of the present invention provides a nanotube-based adsorption material, which is prepared by the method described in the first aspect.
[0014] The third aspect of the present invention provides the use of the adsorption material described in the second aspect in the resource utilization of waste incineration fly ash, comprising the following steps: S1, after the waste incineration fly ash and water are washed according to the liquid-to-solid ratio (8-10):1, the washed fly ash is obtained by plate and frame filter pressing; S2: The washed fly ash and water obtained in S1 are added into a ball mill at a liquid-to-solid ratio of (2-3):1, and at the same time, a nanotube-based adsorption material accounting for more than 3% of the weight of the washed fly ash is added. The nanotube-based adsorption material is divided into three parts and added three times. After ball milling for a period of time, a mixed solution is obtained; S3. After the mixed liquid is filtered through plate and frame, the solid is the waste incineration fly ash which can be recycled.
[0015] The heavy metal leaching in the waste incineration fly ash after the above treatment meets the GB9878 standard. In the subsequent resource utilization, the relevant heavy metal indicators of related products can also meet the environmental protection requirements.
[0016] In some embodiments of the present invention, the amount of adsorbent material added is 3%-6% of the mass of the washed fly ash, and is added in three times, with each addition ratio being 1%-2%.
[0017] In some embodiments of the present invention, the ball mill has a ball milling speed of 500-600 rpm, a ball-to-material ratio of (8-10):1, and a ball milling time of 1-3 hours. In some specific embodiments, the ball mill is a planetary ball mill.
[0018] In some embodiments of the present invention, the detoxified fly ash after ball milling is used in the preparation of building materials, such as building blocks, building filling materials, building cement raw materials, unburned bricks, etc.
[0019] Beneficial effects of the present invention Compared with the prior art, the present invention has the following beneficial effects: The present invention firstly changes the dispersion characteristics of carbon nanotubes by acid modification, then utilizes ultrasound to further increase the dispersion of carbon nanotubes, and then obtains a heavy metal adsorption material with strong adsorption capacity by a latex method; the prepared heavy metal adsorption material realizes the stabilization of heavy metals in fly ash by a coupled mechanochemical method, and the leaching of heavy metals in fly ash meets the requirements of GB9878 standard, and in its resource utilization, further improves the quality of fly ash resource products such as building blocks, building filling materials, building cement raw materials, unburned bricks and the like, and avoids heavy metal pollution caused by the leaching of heavy metals during use.
[0020] The preparation method of the present invention is simple and can be applied to the control of heavy metals in fly ash in various scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The SEM images of carbon nanotubes before and after acid modification are shown, wherein A is the original carbon nanotubes and B is the acid-modified carbon nanotubes; Figure 2 The XRD patterns of carbon nanotubes before and after acid modification are shown. DETAILED DESCRIPTION
[0022] The following examples are used to demonstrate preferred embodiments of the present invention. It will be appreciated by those skilled in the art that the techniques disclosed in the following examples represent techniques discovered by the inventors that can be used to implement the present invention and therefore can be considered as preferred embodiments of the present invention. However, it will be appreciated by those skilled in the art based on this specification that many modifications may be made to the specific embodiments disclosed herein and still achieve the same or similar results without departing from the spirit or scope of the present invention.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs, and the materials cited herein and those cited by them are incorporated by reference. Those skilled in the art will recognize or will learn through routine experimentation that there are many equivalents to the specific embodiments of the invention described herein. Such equivalents are intended to be encompassed by the claims.
[0024] The technical solution of the present application is further described in detail below in conjunction with specific implementation methods.
[0025] Example 1 1. The preparation of adsorption material includes the following steps: (1) The average length of carbon nanotubes is 5 nm. The mixture is mixed in a ratio of 1 g carbon nanotubes: concentrated sulfuric acid: concentrated nitric acid = 250 mL: 80 mL and ultrasonicated for 30 min. Then, it is refluxed at 70 °C for 5 h. After cooling and dilution, it is filtered with a 0.22 μm polytetrafluoroethylene filter membrane and washed with distilled water until the sample is neutral. Finally, it is dried in a vacuum oven at 100 °C for 4 h and ground to obtain acid-modified carbon nanotubes.
[0026] (2) The obtained acid-modified carbon nanotubes were mixed and stirred in a weight ratio of acid-modified carbon nanotubes: zinc oxide: water: stearic acid: gum arabic = 1:1:140:1:1.5, and ultrasonicated for 30 min. Subsequently, 50 g of natural rubber latex was added and stirred for 30 min, and ultrasonicated for 30 min to obtain a mixed solution.
[0027] (3) The obtained mixed solution was dried in a vacuum drying oven at 100°C for 6 hours; then, it was calcined and carbonized in a muffle furnace at 800°C for 6 hours; the carbonized adsorbent was ground in a mortar and passed through a 200-mesh size to obtain the final adsorbent material.
[0028] 2. The application of adsorption materials in waste incineration fly ash includes the following steps: (1) The waste incineration fly ash and water were washed for 1 hour at a liquid-to-solid ratio of 10:1. The washed fly ash was previously obtained by plate and frame filter pressing.
[0029] (2) The washed fly ash and water were added into a planetary ball mill at a liquid-to-solid ratio of 2:1, and the ball mill speed was 500 rpm. The ball-to-solid ratio was 10:1. The heavy metal adsorption material obtained above was added at 3% of the mass of the washed fly ash. The adsorption material was added in 3 times, and the ratio of each addition was 1%. After a period of ball milling, a mixed solution was obtained.
[0030] (3) The mixed liquid obtained in the previous step is filtered through a plate and frame filter to obtain ball-milled fly ash, which can be used in subsequent building materials and other products.
[0031] Example 2 The method steps are consistent with those of Example 1, except that in the preparation step (1) of the adsorbent material, the average length of the carbon nanotubes is 5 nm, and the mixture is mixed in a ratio of carbon nanotubes: water = 1 g: 300 mL, and ultrasonication is performed for 30 min.
[0032] Example 3 The method steps are consistent with those of Example 1, except that in the step (1) of preparing the adsorbent material, the average length of the carbon nanotubes is 15 nm.
[0033] Example 4 The method and steps are consistent with those of Example 1, except that: in the preparation step (1) of the adsorbent material, the average length of the carbon nanotubes is 5 nm, and the mixture is mixed in a ratio of carbon nanotubes: concentrated sulfuric acid: concentrated nitric acid = 1 g: 250 mL: 80 mL, refluxed at 70° C. for 5 h, cooled and diluted, filtered with a 0.22 μm polytetrafluoroethylene filter membrane, and washed with distilled water until the sample is neutral; finally, dried in a vacuum drying oven at 100° C. for 4 h, and ground to obtain acid-modified carbon nanotubes.
[0034] Example 5 The method and steps are the same as those in Example 1, except that: in the preparation step (2) of the adsorbent material, the obtained acid-modified carbon nanotubes are mixed and stirred in a weight ratio of acid-modified carbon nanotubes: zinc oxide: water: stearic acid: dispersant = 1:1:140:1:1.5, and ultrasonicated for 30 minutes, and then 50g of natural latex is added and stirred for 30 minutes, and ultrasonicated for 30 minutes to obtain a mixed solution. The dispersant is a mixed solution of gum arabic and sodium dodecylbenzene sulfonate in a ratio of 1:1.
[0035] Example 6 The method and steps are consistent with those of Example 1, except that: in the preparation step (2) of the adsorbent material, the obtained acid-modified carbon nanotubes are mixed and stirred in a weight ratio of acid-modified carbon nanotubes: zinc oxide: water: stearic acid = 1:1:140:1, and ultrasonicated for 30 minutes, and then 50 g of natural latex is added and stirred for 30 minutes, and ultrasonicated for 30 minutes to obtain a mixed solution.
[0036] Example 7 The method steps are consistent with those of Example 1, except that: in the step (2) of applying the adsorbent material to waste incineration fly ash, the washed fly ash and water are added to a planetary ball mill at a liquid-to-solid ratio of 2:1 for ball milling. The ball milling speed is 500 rpm and the ball-to-material ratio is 10:1. At the same time, the heavy metal adsorbent material obtained above is added. The adsorbent material is 6% of the mass of the washed fly ash and is added in 3 times, with each addition ratio being 2%. After ball milling for a period of time, a mixed solution is obtained.
[0037] Example 8 The method and steps are consistent with those of Example 1, except that: in the step (2) of applying the adsorbent material to waste incineration fly ash, the washed fly ash and water are added to a planetary ball mill at a liquid-to-solid ratio of 2:1 for ball milling. The ball milling speed is 500 rpm and the ball-to-material ratio is 10:1. At the same time, the heavy metal adsorbent material obtained above is added. The adsorbent material is 1.5% of the mass of the washed fly ash. The adsorbent material is added in three times, and the ratio of each addition is 0.5%. After ball milling for a period of time, a mixed solution is obtained.
[0038] Example 9 The method steps are consistent with those of Example 1, except that: the obtained washed fly ash is stirred evenly at a liquid-solid ratio of 2:1, and the heavy metal adsorption material obtained above is added at the same time, the adsorption material is 3% of the mass of the washed fly ash, and is added in 3 times, each time at a ratio of 1%; after stirring for a period of time, a mixed solution is obtained.
[0039] Performance Comparison (1) Comparative analysis of carbon nanotubes before and after acid modification, where the SEM images are shown in Figure 2. Figure 1 As shown, the XRD pattern is Figure 2 As shown; wherein A is the original carbon nanotube and B is the acid-modified carbon nanotube.
[0040] The results show that: It can be seen from XRD that the characteristic peaks at 25.7°, 42.6° and 53.6° correspond to the characteristic peaks of graphite. Among them, the characteristic peak at 25.7° has an increased peak area after modification, indicating that acid modification can improve the graphitization degree of carbon nanotubes. In addition, the characteristic peak at 45.6° can be attributed to the characteristic peak of the metal in the catalyst, and its peak intensity decreases after acid modification, indicating that the residual impurities in the carbon nanotubes are further processed and the purity of the carbon nanotubes is improved.
[0041] (2) The heavy metal content in the fly ash prepared in Examples 1 to 9 was tested by leaching method. The test results are shown in Table 1.
[0042] Table 1 Heavy metal detection data in the fly ash prepared in Examples 1 to 9
[0043] Note: ND means below the upper limit of detection and not detected by the device.
[0044] The test results show that the pass rate of the 10 heavy metals in the original fly ash is only 50%. Among them, the contents of heavy metals Cd, Cu, Ni, Pb and Zn exceed the GB9878 standard, and Cd exceeds the standard by 224%, Cu exceeds the standard by 200.4%, Ni exceeds the standard by 51.1%, Pb exceeds the standard by 760.1% and Zn exceeds the standard by 399.1%.
[0045] After the adsorption material prepared in this application was added to the fly ash for treatment, the qualified rate of the corresponding 10 heavy metals in the obtained fly ash reached 100%, reaching the GB9878 standard.
[0046] In the process of formulating the plan, we explored the effects of different treatment methods on the final fly ash and found that the heavy metal compliance rate in the final fly ash was only 50% without acid modification, the heavy metal compliance rate in the final fly ash was only 60% without dispersant, and the heavy metal compliance rate in the final fly ash was only 70% without ultrasonic treatment or ball milling of fly ash and adsorption material during the preparation of adsorption materials. The length of carbon nanotubes has little effect on the final result, and the heavy metal compliance rate in fly ash is 90%.
[0047] In the process of exploring the amount of adsorption material added, it was found that the greater the amount added, the better the stability of heavy metals in fly ash. Adding 6% adsorption material to treat fly ash is equivalent to adding 3% adsorption material, and the leaching of heavy metals in fly ash is less. However, from an economic point of view, the addition ratio should not be too high. Adding 3% can make the leaching of heavy metals in fly ash meet the standard requirements.
[0048] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as references separately. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined in the present application.
Claims
1. A method for preparing an adsorbent material based on nanotubes, characterized in that: The steps include: S1. Mix the carbon nanotubes and the acid solution in the ratio of carbon nanotubes: concentrated sulfuric acid: concentrated nitric acid = 1 g: 250 mL: (50-80) mL, and perform ultrasonic treatment; reflux at 60-70°C for 5-6 h, cool and dilute, filter with a filter membrane, wash with distilled water until neutral, dry in a vacuum drying oven, and grind to obtain acid-modified carbon nanotubes; S2, the obtained acid-modified carbon nanotubes are acid-modified carbon nanotubes according to the weight ratio: Zinc oxide: water: stearic acid: dispersant = 1: (0.5-1): (130-150): (1-1.2): (1-1.5) are mixed and stirred, ultrasonicated, 50-70 g of natural latex is added and stirred evenly, ultrasonicated again to obtain a mixed solution; S3, the mixed solution is dried in a vacuum drying oven and then calcined and carbonized; the carbonized adsorbent is ground in a mortar and passed through 200-250 meshes to obtain the final adsorption material.
2. The method according to claim 1, characterized in that: The dispersant is one or both of gum arabic and sodium dodecylbenzene sulfonate.
3. The method according to claim 1, characterized in that: In the steps S1 and S2, the ultrasonic time is 30-60 min.
4. The method according to claim 1, characterized in that: In step S1, the drying temperature is 90-100° C. and the drying time is 4-8 hours.
5. The method according to claim 1, characterized in that: In the step S1, the filter membrane is a 0.22 μm polytetrafluoroethylene filter membrane.
6. The method according to claim 1, characterized in that: In the step S3, the calcination temperature is 800-850° C., and the carbonization time is 4-6 hours.
7. The method according to claim 1, characterized in that: The length of the carbon nanotube is 2-10 nm.
8. A nanotube-based adsorption material, characterized in that: The method is prepared by any one of claims 1 to 7.
9. The use of the adsorption material according to claim 8 in the resource utilization of fly ash from waste incineration, characterized in that: The method comprises the following steps: S1, after the waste incineration fly ash and water are washed according to the liquid-to-solid ratio (8-10):1, the washed fly ash is obtained by plate and frame filter pressing; S2, the washed fly ash and water obtained in S1 are added to a ball mill at a liquid-to-solid ratio of (2-3):1, and at the same time, the adsorption material of claim 8 is added, accounting for more than 3% of the mass of the washed fly ash, and the adsorption material is divided into three parts and added three times, and a mixed liquid is obtained after ball milling for a period of time; S3. After the mixed liquid is filtered through plate and frame, the solid is the waste incineration fly ash which can be recycled.
10. The application according to claim 9, characterized in that: The ball-to-material ratio of the ball mill is (8-10):1, and the ball milling time is 1-3h.
Citation Information
Patent Citations
Zinc-containing multielement metallic oxide / carbon nanotube complex as well as preparation method and application thereof
CN101711971A
Composite ceramic filter core and preparation method thereof
CN102924067A
Carbon nanotube / zinc oxide PTFE film and preparation method thereof
CN105749981A
Rubber masterbatch, method for producing same, and rubber composition obtained from same
CN108203522A
Preparation method of carbon nanotube composite material
CN111187454A